NUMERICAL SIMULATIONS OF FLOW ROUTING IN A CANAL USING SAINT VENANT EQUATIONS - Agus Sulistyono, Bambang
A canal with a rectangular cross section is flowing water from upstream. By utilizing the discharge data that enters the canal, it can be routed / predicted the amount of discharge and water level elevation at the specified location in the downstream area using the Saint Venant equations. In this study, routing the amount of discharge and elevation of the water level at the specified location in the downstream area due to the hydrograph inflow was carried out on two canal forms, namely homogeneous canal and nonhomogeneous canal. The simulation of routing the magnitude of discharge and elevation of the water level in homogeneous canal was done using a simplified model. This simplified model is a mathematical model obtained from the Saint Venant equations by modifying its momentum equation so that the momentum equation has only two flow variables, namely discharge and wet cross-sectional area. This simplified model is solved numerically using the finite difference method. The main results of this stage are data on peak discharge and peak water level at the specified location. To reduce the peak of the discharge and the peak of the water level elevation at the specified location in the downstream area, in this study developed the existence of a flood pocket. The flood pocket serves to accommodate and hold the water flow so that in the specified location a decrease in the discharge peak and the peak of the water level. The mathematical model used for simulations on the nonhomogeneous canal is the dynamic model. This dynamic model is solved numerically using the finite volume method on grid staggered. Based on the results of the simulation it can be concluded that the numerical scheme of the grid staggered that is used is really able to simulate the physical properties of the flood pocket, which is reducing the peak discharge and peak water level elevation. In practice, if the discharge input is a flood hydrograph occurring upstream, then the results of numerical calculations can be used as supporting data on the flood control and warning system delivered to residents along the canal. Or suppose there is a river to be given a dike, then the information obtained from the calculation of the peak water level is very helpful for determining the height of the dike's peak.